Manajemen Pendidikan Islam Anak-anak Pra Sekolah Berbasis Qur’ani - Nurhadi Nurhadi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
The pattern of educating children or the method of educating children from before birth to school age is a necessity for a mother. Mother is the first and main geographical teacher in pre-school children's education. The age of toddlers to pre-school for children is golden age. Learning while playing is a certainty, playing is the first education for children under five. The age of a toddler is like a blank cassette that can store and record something that is accustomed to and experienced in the development of a child's life. For parents, if they expect their children to become children who are good enough to have to have insight and knowledge of management of pre-school children's education. Among the many models and patterns of education management, the easiest way to deliver children to become good and noble children is quran-based management. Al-Qur'an is a holy book from the most holy God, it will be easily digested and accepted by the core of the teachings to children who are still pure. In terms of management of the pre-school education based on the Qur'an, it is intended for parents to plan for their children to always listen to the chants of the Qur'an. Then group them into playing the verses in the form of per juz al-Qur'an in one month. Then the parents evaluate the child who has been refreshed by the Qur'an, if the chanting is paused, what will happen to the child's reaction. If you cry, it means that the spirit of the Qur'an has entered your heart and soul. The situation is valid for 30 juz, so the child for 30 months has listened to and recorded 30 juz verses of the Qur'an, God willing, the age of pre-school children has been memorized and will be smart with the waslah verse of the Qur'an. This is a Qur'ani-based management that gives birth to children who love and love to read the Qur'an and the hafidz of the Qur'an.